The understanding of household food security among glutinous rice smallholder farmer in Langkawi, Malaysia - Jayanti Eka Wardani, Nur Afifah Septiana; Jamaluddin, Askiah; Zainal Badari, Shamsul Azahari (Human Resource Management Academic Research Society, 2023)
Malaysia has 44 of the population who are rural communities with smallholder farmers. Langkawi is one of the districts in Kedah with the potential for glutinous rice production. However, food security still occurs in areas such as Langkawi because of the price and market accessibility. The objective of this research is to examine the financial status of households and their access to sufficient food by utilizing the food poverty line. Additionally, it seeks to explore the connection between different sources of household income (total household income, respondent's income, and wife's income) and the availability of food in local markets. Respondents were selected according to a list of names of smallholder farmers who participated in the glutinous rice planting program. There are 118 respondents from eight villages in Langkawi was all population (census). The finding shows that the household income has a significant relationship with household food security using Pearson correlations (Household income = 0.08, respondent’s income = 0.00, wife’s income = 0.03). The findings of this study can be applied as a first step to addressing poverty and food insecurity among Langkawi small farmers participating in the glutinous rice program. In addition, it helps identify important elements that affect food safety.